Validitas Dan Reliabilitas Instrumen Observasi Terhadap Penilaian Teknik Servis Atas Dalam Sepaktakraw - Marpaung, Hakim Irwandi; Atmaja, Danuditya Purna; Purba, Rismaidah; Ghurri, Ainul (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2023)
This research is to assist coaches in assessing the technical implementation of serves and their relationship to achieving the main aspects of service movements in sepaktakraw. The purpose of the study is to validate the observation instrument to assess the technical implementation of the top service in Sepaktakaw. This observation instrument can be used to assess progress in relation to achieving important aspects of movement in each service. Methods: Construction of the validity and reliability of this observation instrument is carried out in four phases. The first phase is the study of literature that specifically review the construction of observation instruments. The second stage, the instrument construction was established. The third stage, the validity coefficient of the instrument's content is determined by Aiken V and 9 experts with qualifications, level of understanding, conformity of words, and relevance of the statement, etc. (with a rating scale of 1-4). The internal validation of the instrument is calculated and applied by 18 athletes, quantitatively tested using the product moment correlation. The fourth stage, the reliability of the instrument is calculated using Cronbach's Alpha reliability test. Results: The result of this study indicates that the instrument has optimal value of content and internal validity. In addition, the instrument also has a high reliability value. Conclusion: The results of this study can be used in similar circumstances. More than that, these instruments can be considered measuring instruments to be utilized by the trainer, the teacher as an assessment of the ability of top service techniques